ANALISIS NILAI PERUSAHAAN PADA SEKTOR FOOD AND BEVERAGES DI BURSA EFEK INDONESIA - Susilo, Alifia Safa; Nur, Dhani Ichsannudin (JURNAL MANAJEMEN AKUNTANSI (JUMSI), 2021)
Firm value is the company's performance, which is reflected in the share price that is formed by supply and demand in the capital market. The purpose of this study is to determine and analyze the effect of leverages, profitability, company size, and company growth as factors that influence a firm value in food and beverages companies listed on the Indonesia Stock Exchange in the 2015-2019 period. The population used in this study were 27 companies. The sampling method in this study was purposive sampling. The sample wereÂ 17 companies. The method used in this research is multiple linear regression with the classical assumption test. The results indicate that the independent variables, namely profitability, company size, and company growth can contribute to increasing the value of companies. While, leverages cannot contribute in increasing the value of company.Â